Sectoral Allocation of Foreign Aids and Poverty Alleviation in Nigeria, 2010-2020 - Obiora, Charles Arinze; Nwanolue, Bonn Obiekwe Godwin; Okeke, Christian Chidi (International Journal of Culture and History, 2024)
The study was necessitated by the high rate of poverty in Nigeria regardless of the foreign aids inflow into the country from 2010 to 2020. Whereas the country received foreign aids which could have resulted in poverty alleviation within the period of this study, she antithetically witnessed increase in poverty rate to the extent that the World Bank in May 2018 reported that Nigeria had emerged poverty capital of the world. According to the National Bureau of Statistics’ report, over 82.9 million persons, representing about 40.1 percent of the total population, were considered poor by national standards as at 2019. The poverty challenge inspite of the foreign aids inflow into Nigeria therefore necessitated the question on how sectoral allocation of foreign aids contributed to poverty alleviation in Nigeria from 2010 to 2020. Anchored on the Big Push Theory, the study adopted ex-post facto research design and documentary method for data collection. Qualitative descriptive method was used for data analysis. Among other things, the study found out that sectoral allocation of foreign aid resources did not contribute to poverty alleviation in Nigeria from 2010 to 2020 as those sectors critical for poverty alleviation did not receive massive investments. On the contrary, the foreign aids were split among numerous (consumption) sub-heads which rendered the aids incapable of contributing to poverty alleviation in the country. In view of the findings, the study therefore recommended the need to channel future foreign aids inflow into projects with high capital returns or the productive sectors of the economy in order to achieve a positive outcome on poverty alleviation.